sports culture one student one sport policy in malaysia - Saryono, Gunathevan Elumalai dan (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2015)
Sport and fitness is becoming more and more important in the lives of every human on the earth. Sports should beintegral in a person’s life. This is due to the benefits derived in terms of health and to increase their mastery of natureand the environment (WHO 2010). Sport involves basic human skills which are developed and exercised for theirown sake, in parallel with several advantages and benefits. Centers for Disease Control and Prevention, (2010),emphasised the risk of insufficient sport and physical activities in adolescents which lead to negative effect on healthand fitness. Malaysia has a long history in sports, unfortunately in recent years; the glory dwindled due to the society’schanging lifestyle. This phenomenon has prompted the government to form a new policy promoting the school PhysicalEducation and sporting activities. Malaysian Education Ministry has launched “One Student One Sport” policy on9th of June 2011, which focused on producing and developing a well balanced student in terms of physical, emotion,spiritual and intellect. The policy is in line with the National Sports Policy to cultivate sports in the community, and wasstarted in schools through two strategies, that is “Sports For All and Sports For Excellence.” One of the aims includenurturing human capital through wholesome participation amongst students in sports throughout the year, cultivatinga sporting culture so that they become a member of the society with an active, balanced and healthy lifestyle, forminggood values and self-discipline and creating a track record towards sporting excellence. The purpose of the policy isto move towards a balanced development of body and mind of our young ones. At the same time, it hopes to instillhealth and vitality into the sports culture in schools. But, the success of “one student, one sport” policy depends onthree factors. First, the Education Ministry must try to meet the needs of sports facilities and equipments. The secondfactor is that the number of sports periods must be increased. Third, the Physical Education curriculum design alsorequires some changes in order to attract the interest of students and make it as a culture in their life.Key Word: one sport, one student, policyAbstrakOlahraga dan kesehatan kini menjadi hal yang semakin penting dalam hidup setiap manusia di dunia. Olahragaseharusnya bersifat integral bagi kehidupan manusia. Hal ini dikarenakan manfaat yang akan diperoleh untukkebugaran tubuh dan keterampilan memahami alam dan lingkungan (WHO 2010). Olahraga meliputi kemampuandasar manusia, yaitu berkembang dan bergerak untuk kepentingan manusia itu sendiri. Kegiatan ini bersifat paraleldengan berbagai keuntungan dan manfaat yang didapat. Centers for Disease Control and Prevention, (2010),menekankan pada resiko aktivitas fisik dan olahraga, yang tidak cukup bagi orang dewasa, yang mampu mengarahkepada efek negatif bagi kesehatan. Malaysia memiliki sejarah yang panjang dalam dunia olahraga. Namun sayangnyabeberapa tahun belakangan, kejayaan dunia olahraga tergeser dengan gaya hidup masyarakat yang berubah. Hal inimendorong pemerintah untuk membentuk kebijakan baru yang bertujuan mengenalkan mata pelajaran PendidikanJasmani dan olahraga ke berbagai sekolah.Kementerian Pendidikan Malaysia telah mengeluarkan kebijakan “OneStudent One Sport” atau “Satu Siswa Satu Olahraga” pada 9 Juni 2011. Fokus kebijakan ini yaitu menghasilkan danmengembangkan kemampuan siswa untuk memiliki keseimbangan tubuh yang baik dan kecerdasan jasmani, emosi,spiritual, dan intelektual. Kebijakan ini sesuai dengan misi Kebijakan Olahraga Nasional untuk memperkuat olahraga diberbagai komunitas. Misi ini dimulai dari sekolah melalui dua strategi, yaitu “Sport for All and Sport for Excellence“ atau“Olahraga untuk Semua dan Olahraga untuk Keunggulan.” Adapun tujuannya antara lain untuk membina siswa melaluipartisipasi yang menyeluruh, memperkuat budaya olahraga sehingga mereka mampu menjadi anggota masyarakatyang aktif, menyeimbangkan gaya hidup sehat, membentuk disiplin diri dan nilai-nilai terpuji, serta menghasilkan rekam jejak yang unggul dalam bidang olahraga.Tujuan kebijakan “One Student One Sport” adalah untuk membentuk jiwadan raga yang seimbang dalam diri generasi muda. Selain itu, kebijakan ini diharapkan mampu melestarikan budayaolahraga di sekolah untuk menjaga kesehatan tubuh. Namun, keberhasilan kebijakan ini membutuhkan tiga faktorpendukung. Pertama, Kementerian Pendidikan harus berusaha memenuhi kebutuhan akan peralatan dan fasilitasolahraga. Kedua, jam olahraga harus ditingkatkan. Ketiga, rancangan kurikulum Pendidikan Jasmani perlu dimodifikasiagar mampu menarik minat para siswa dan menjadikan olahraga sebagai budaya hidup mereka.Kata Kunci: satu olahraga, satu siswa, kebijakan